A novel model and design of a MEMS Stirling cooler for local refrigeration - Bégot Sylvie (EDP Sciences, 2021)
In this paper, we present a new model design and parametric studies of a miniature Stirling cooler machine for on-site refrigeration. The MEMS (Microelectromechanical systems) technology is investigated to design this machine. The concept could be used to provide cooling at chip scale and mitigate hot spots in electronic devices. Whereas numerous works deal with Stirling engines at a macroscopic scale, only a few works concern miniaturized Stirling engines. Therefore, a model analysis giving insights of the impact of the technological choices and downsizing of the machine is needed. A base design model is presented. The model results lead to a cooling power of 10 mW and a Coefficient Of Performance of 1.45. A parametric study is conducted for operational and design parameters. Compared to macro-scale design, the same trend is observed for the influence of the thermal performance regenerator. Different trends from macroscopic engines were observed for hysteresis losses importance, and the choice of the working gas. The raise in power due to the raise in frequency expected for micro-scale devices is counterbalanced by the degradation of the COP due to the increase in thermofluidic losses. Squeeze film damping and finite speed losses can be neglected at this scale.